Two summers of São Paulo drought: Origins in the western tropical Pacific - Seth, A.; Fernandes, K.; Camargo, S.J. (Wiley, 2015)
Two years of drought in Southeast Brazil have led to water shortages in São Paulo, the country's most populous city. We examine the observed drought during austral summers of 2013/2014 and 2014/2015 and the related large‐scale dynamics. The 2013–2014 precipitation deficits were more concentrated in the state of São Paulo, while in 2014–2015 moderate deficits were seen throughout the region. We find that a persistent warm sea surface temperature (SST) anomaly in the western tropical Pacific Ocean was an important driver of drought via atmospheric teleconnection in the two December–February seasons. The warm SST and associated convective heating initiated a wave train across the South Pacific. The resulting anticyclonic geopotential height anomaly over the southwest Atlantic expanded the westward margin of the South Atlantic high and prevented low‐pressure systems from entering southeast Brazil from midlatitudes. This mechanism suggests a hemispheric symmetry to that proposed for the recent California drought.